Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/2158244021994802
|View full text |Cite
|
Sign up to set email alerts
|

Economic Crisis and Professions: Chartered Accountants in Zimbabwe

Abstract: This study examined the effects of a declining economy on the profession of chartered accountants (CAs) in Zimbabwe. The study adopted a qualitative approach using a pragmatic grounded theory design. Primary data were obtained through in-depth interviews with five purposively sampled CAs and two key informants drawn from the professional body and an institution that trains CAs. Furthermore, secondary data were drawn from the professional body’s archives and from newspapers. Data from interviews and documents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…In their study in South Africa, Fataar & Norodien-Fataar (2021) observed that digital technology has been a ubiquitous, albeit uneven, feature of educational platforms for at least 40 years, growing exponentially over the last 20. However, in Zimbabwe, technical development has been stalled by the economic crisis (Maunganidze et al, 2021) and the digital divide between developed and developing nations has become more conspicuous in the wake of the Covid-19 pandemic given that most universities in African countries have struggled to provide comprehensive online education packages during this period. Although e-learning offers prospects for social inclusion, in the Zimbabwean case, it further intensified social exclusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their study in South Africa, Fataar & Norodien-Fataar (2021) observed that digital technology has been a ubiquitous, albeit uneven, feature of educational platforms for at least 40 years, growing exponentially over the last 20. However, in Zimbabwe, technical development has been stalled by the economic crisis (Maunganidze et al, 2021) and the digital divide between developed and developing nations has become more conspicuous in the wake of the Covid-19 pandemic given that most universities in African countries have struggled to provide comprehensive online education packages during this period. Although e-learning offers prospects for social inclusion, in the Zimbabwean case, it further intensified social exclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Outputs: University graduates pedagogical processes. However, for Zimbabwe, the operating environment for universities was further exacerbated by the economic crises prevailing in the country (Maunganidze et al, 2021). According to the African Development Bank (2021), before the Covid-19 pandemic, Zimbabwe's economy was already in recession, contracting by 6.0% in 2019.…”
Section: Transformation Process: Online Teaching and Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…This is despite Zimbabwe's latest unemployment rate soaring to 85% as of 2014 (Rusvingo 2015). The unemployment figures have remained more or less the same over the past six years (see Maunganidze, Bonnin, and Ruggunan 2021).…”
Section: Notesmentioning
confidence: 97%
“…In 1997, The government decided to pacify the situation by awarding the war veterans a once-off payment of $50 000 in local currency which was equivalent to US$4,205 (Chipaike and Mhandara, 2013:150). Maunganidze et al (2021) argue that this was one of the misinformed economic decisions that plunged the economy into a crisis. The pressure for land redistribution continued to mount and as such the government was forced to act.…”
Section: Zimbabwe's Bilateral Relations With the Usmentioning
confidence: 99%